2022
DOI: 10.3390/foods11060847
|View full text |Cite
|
Sign up to set email alerts
|

Formulation Strategies for Improving the Stability and Bioavailability of Vitamin D-Fortified Beverages: A Review

Abstract: Vitamin D is a lipophilic bioactive that plays an important role in bone health. Fortification of beverages, such as milk, fruit juices, teas, and vegetable drinks, could be an efficient strategy to prevent vitamin D deficiency and its associated effects on health. This review summarizes the current understanding of beverage fortification strategies with vitamin D and the resulting effects on the stability, bioaccessibility, and sensory properties of the formulated products. The direct addition technique has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 75 publications
0
12
0
3
Order By: Relevance
“…For example, using a rat as an animal model, a study found that spherical particles up to 5 µm in diameter can be absorbed through the intestines when locally delivered, and those up to 1 µm can be absorbed when orally administered [55]. Other delivery systems (such as microemulsions or some microcapsules) can even exist at sizes up to 5000 µm in diameter [35,56]. Such systems can be referred to as microcapsules, defined by Vieira and Souza as having diameters between 1-5000 µm [56].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, using a rat as an animal model, a study found that spherical particles up to 5 µm in diameter can be absorbed through the intestines when locally delivered, and those up to 1 µm can be absorbed when orally administered [55]. Other delivery systems (such as microemulsions or some microcapsules) can even exist at sizes up to 5000 µm in diameter [35,56]. Such systems can be referred to as microcapsules, defined by Vieira and Souza as having diameters between 1-5000 µm [56].…”
Section: Discussionmentioning
confidence: 99%
“…Other delivery systems (such as microemulsions or some microcapsules) can even exist at sizes up to 5000 µm in diameter [35,56]. Such systems can be referred to as microcapsules, defined by Vieira and Souza as having diameters between 1-5000 µm [56]. The current iteration of LipoMicel falls under this category.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, vitamin D shows some degree of stability when it comes to oxidation and acid, and the stability suffers under various factors such as light, pH, storage time, temperature, and humidity [134]. Encapsulation has been pointed out as desirable delivery approach not only to improve on stability but also preserve bioactivity,, and greatly enhance its absorption in beverage systems [135].…”
Section: Vitamin Dmentioning
confidence: 99%
“…Liprotides can release Vitamin D by transferring Vitamin D to phospholipid vesicles. Vitamin D encapsulated by liprotides using α-lactalbumin-oleic acid and β-lactoglobulin can increase the availability of Vitamin D in clear beverage products with neutral pH [75]. Many compounds can be used to form a liprotides system, but there is a specific component that has been developed to form a liprotides system such as α -lactalbumin, β-lactoglobulin, and oleic acid.…”
Section: Liprotidementioning
confidence: 99%